The susceptibility test of vaginal yeasts and their relationship with the age in Iraqi women - Baghdad Science Journal (مجلة بغداد للعلوم, 2010)
This study aims to isolate the pathogenic yeasts from genital tract and investigate their relationship with the age .The results clarified that the most pathogenic yeast isolated from genital tract was Candida albicans , also the results of C.albicanas isolates susceptibility test, to different antifungal revealed that they were sensitive to Miconazole, Ketoconazole and Clotrimazol and were resistant to Nystatin and Grisofulvin. The study of relationship of vaginal infection with the age showed that the incidence of infection with Candida was high among females age group (19-39 years).